Multicolour object detection using multithreading - Saaidon, Nur'Ain; Sediono, Wahju (2015)
As image and video processing applications are leaning towards real-time requirement, the program control for the system must be designed efficiently while taking the processing time factor as one of the main considerations. This paper presents the method of detecting multicolour objects and the processing time comparisons of designed algorithms. Algorithm with multithreading approached is compared to the usual sequential approach of image processing. The number of threads created in multithreading’s algorithm is depending on the number of colours to be detected. Time processing for multicolour object detection using multithreading is shown to be significantly less compared to sequential process as the number of detected colours increases. Multithreading programming method are useful to improve efficiency of the system’s application and take the benefit offered by multicore processor in most of the computer nowadays.